Association between endurance of the trunk extensor muscles and balance performance in community-dwelling older adults: a cross-sectional analysis - Flora, Sofia (2022)
Background/Aims: Previous research has disregarded the performance of the extensor muscle group of the trunk in balance control. The main purpose of this exploratory study was to assess the association between balance performance and endurance of the trunkextensor muscles in older adults, considering possible co-factors such as age and body mass index. Methods: A correlational and predictive cross-sectional study was conducted with 61 community dwelling older adults (women n=45) with a mean age of 71 years (± standard deviation 6 years), and a mean body mass index of 28.1 kg/m2 (± standard deviation ± 4.7 kg/m2). The Berg Balance Scale was used to assess balance performance and Trunk Extensor Endurance Test to assess muscle endurance. Spearman’s correlation coefficients (ρ) and single and multiple regression analyses were performed. Statistical significance was set at 0.05. Results: The largest correlations were found between the Berg Balance Scale score and Trunk Extensor Endurance Test (ρ=0.41, P=0.001) and body mass index (ρ=−0.36, P=0.005). Muscle endurance alone predicted ~10% of the Berg Balance Scale score (R2=0.10, P=0.015). When combined with body mass index, it accounted for ~19% (R2=0.19, P=0.002). Adding the remaining variable (age) to the previous model increased the prediction by ~3% (R2=0.22, P=0.002). Conclusions: Muscle endurance and body mass index significantly predicted (~19%) balance performance in older adults. Because these are modifiable factors, they should be routinely included in the screening of balance performance in older adults and addressed accordingly in preventive or rehabilitation programmes.